2022
DOI: 10.1002/batt.202200020
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Small Ferromagnetic Fe3O4 Nanoparticles Modified Separator for High‐Rate and Long Cycling Lithium‐Sulfur Batteries

Abstract: As a promising energy storage system with high specific capacity, lithium‐sulfur (Li−S) battery is striving for a high‐rate and longer lifetime. Whereas the slow redox kinetics and the shuttle effect of polysulfides (PSs) still severely restrict the performance of Li−S batteries. Here, a rational designed ferromagnetic Fe3O4 nanoparticles (FM‐Fe3O4 NPs) modified separator is engineered for Li−S batteries. Moreover, the particle size of FM‐Fe3O4 NPs was tuned to enhance the energy storage performance. Consequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Yue et al. also reported an improved LiPS blocking when adding ferromagnetic Fe 3 O 4 nanoparticles into the separator, but no clear relationship between the particles’ ferromagnetism and the enhanced performance was established [36] . Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…Yue et al. also reported an improved LiPS blocking when adding ferromagnetic Fe 3 O 4 nanoparticles into the separator, but no clear relationship between the particles’ ferromagnetism and the enhanced performance was established [36] . Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…[35] Yue et al also reported an improved LiPS blocking when adding ferromagnetic Fe 3 O 4 nanoparticles into the separator, but no clear relationship between the particles' ferromagnetism and the en-hanced performance was established. [36] Li et al proposed a semiliquid Li-LiPS battery using a ferrofluid containing Li 2 S 8 and ferromagnetic γ-Fe 2 O 3 nanoparticles as a flowable catholyte. [37] An applied magnetic field could be used to keep the ferrofluid in close contact with the current collector and potentially to flow the catholyte in a flow battery configuration without the need for pumps.…”
Section: Introductionmentioning
confidence: 99%